Mitochondrial Deficiency Is Associated With Insulin Resistance - Goodpaster, Bret H. (American Diabetes Association, 2013)
The specific cellular underpinnings or mechanisms of insulin resistance (IR) are not clear. Here I present evidence to support a causal association between mitochondrial energetics and IR. A large body of literature indicates that mitochondrial capacity for oxidative metabolism is lower in human obesity and type 2 diabetes. Whether or not mitochondria play a causal role in IR is hotly debated. First, IR can be caused by many factors, many of which may or may not involve mitochondria. These include lipid overload, oxidative stress, and inflammation. Thus the first tenet of an argument supporting a role for mitochondria in IR is that mitochondria derangements can cause IR, but IR does not have to involve mitochondria. The second tenet of this argument is that animal models in which oxidative metabolism are completely abolished are not always physiologically or pathologically relevant to human IR, in which small metabolic perturbations can have profound effects over a prolonged period. Lastly, mitochondria are complex organelles, with diverse functions, including links with cell signaling, oxidative stress, and inflammation, which in turn can be connected with IR. In summary, mitochondrial “deficiency” is not merely a reduced energy generation or low fatty acid oxidation; this concept should be expanded to numerous additional important functions, many of which can cause IR if perturbed.